The consequences of the implementation of the Royal Decree-Law of sanitary regulation RD 16/2012 on migrant women’s health - Morero Beltrán, Anna; Ballesteros Pena, Ana (Investigaciones Feministas (Feminist Research), 2015)
The Royal Decree-Law 16/2012 for sanitary regulation, led to the elimination of certain benefits for people not registered in the Spanish National Security Social System. Thus, this means the end of the universal and free health care for all citizens who live in Spain. This recent regulation creates an unequal access to a recognized basic human right. This paper aims to provide an assessment of the impact of the elimination of such health care rights for immigrant people, specifically by exploring their implications for immigrant women, and the consequences of the implementation of the Royal Decree-Law on violence against women and on sexual and sexual and reproductive rights. In addition, this paper also seeks to collect the efforts of organizations who work in defense and for the vindication of the universality of the health in Spain. This paper will address, particularly, the case of Catalonia.